The effect of applying artificial intelligence in brand marketing strategies to improve company effectiveness and efficiency (case study: j.co coffee & donuts Indonesia) - Arliza Anastiawan Sabili; Arvidhia Khalisa; Rima Kusumah Dewi (Sean Institute, 2024)
This article aims to explain and analyze the basic concepts of artificial intelligence or AI and identify areas of AI that can be applied digitally in the marketing field. At this time, AI has an important role in marketing in the digital world. AI has changed the way companies J.CO Coffee & Donuts create programs and interact with customers. AI is also used to manage advertising. Using literature reviews and examples that have been conducted J.CO Coffe & Donuts, this study explores several important aspects such as AI's ability to analyze customer data and market trends, provide targeted content recommendations, personalize customer experience, improve interaction with chatbots, and apply social media sentiment analysis to understand customer reactions to marketing. The result of this research is that the presence of AI and social media currently provides an opportunity for a product to be able to develop more and reach its market. This research confirms that AI is a powerful and effective tool to improve the effectiveness and success of marketing campaigns.